Technical Construction of Advertisements in Radio of the Republic of Iraq - Rashid Al-Azzawi, Hussein (ALBAHITH ALALAMI, 2012)
Studies and scientific research conducted in the field of communication have shown that broadcasting has a clear impact on the ideas, attitudes and behavior of the masses if it is better used in making the media message studied. The role of this means is not only to present opinions and ideas, but also to influence trends by supporting or changing them. This is of course a matter for the nature of the content in terms of its formulation and the way it is prepared and presented. The power and appeal of a radio message is not complete by simply creating content without creating a distinctive design; and to what extent this content depends on the logic and psychology of persuasion. The conviction of the content and the magnificence of its design is the basis. Therefore, changing trends depend on it; and from these two directions, the basic reality is formed to change the behavior. As of the characteristics of radio that are not available in other means, this increases its effectiveness in attracting attention to it; and increases the possibility of influencing the behavior of the masses. Since research shows that the conviction of the public broadcast message transmitted over the air is very high. And the degree of resistance to this message is less when compared to newspapers. The simplified radio message, moreover, enables the individual to have the ability to retain that message for a longer period compared to the advertising message broadcast through other means. For importance of broadcasting in delivering the audio advertising, the advertisers have been alerted since the emergence of this means in providing advertising message that promotes goods, services and ideas, especially with the increasing competition created by economic, industrial, commercial and technological systems in various fields in the modern era.